Odpowiedzi

  • Użytkownik Zadane
2010-02-10T15:56:56+01:00
A) 3(2x - 1) + 4 (1 - x)=6x-3 + 4- 4x =2x+1

b)2(7x + 5) - 6(x - 2)=14x+10-6x+12=8x+22

c) -2x(8 - x) - 5(x² + 3x)=-16x+2x² -5x²-15x = -31x -3x²

d) 5(3-2x) - (4x +6) *3 =15-10x -12x-18 = -22x -3
2010-02-10T15:58:46+01:00
A. =6x-6+4-4x=2x-2
b. 14x+10-6x-4
c. -16x+2x kwadrat-5xkwadrat+15x=-x-3xkwdrat
d. 15-20x-12 x + 18=8x+33
2010-02-10T15:59:03+01:00
A) 3(2x - 1) + 4 (1 - x)=6x-3+4-4x=2x+1
b)2(7x + 5) - 6(x - 2)=14x+10-6x+12=20x+22
c) -2x(8 - x) - 5(x² + 3x)=-16x+2x²-5x²+15x=-x-3x²
d) 5(3-2x) - (4x +6) *3 =15+10x-4x-6*3=9+6x*3=27+18x